Empowering waqf financing sustainability through capital market in Malaysia: a review - Khaliq, Ahmad; Hussin, Nazimah; Mohd Thas Thaker, Mohamed Asmy; Allah Pitchay, Anwar; Mohd Thas Thaker, Hassanudin (2019)
Though the Waqf (Islamic endowment) has been operative for countless years as a superlative instrument that upholds societal welfare, most of the developed and developing countries are yet to entirely utilize Waqf for the capital market investment. This paper aims to review and explore the Waqf financing feasibility through capital market integration from the Malaysian context. Financing tools primarily designed for Waqf assets development are rigorously explored to secure sustainability of Waqf institutions. While embracing the theory of sustainability entailing chief aspects of economics, social and environment as a guiding principle, the study proposes a viable integration of Waqf and capital market instrument of unit trust investments based on the Shariah-compliant. The finding illustrates that there is an essential need for a novel apparatus through the capital market such Waqf unit trust to realize grander Waqf funds accumulation, investment, and distribution. It is exceedingly encouraged that produced proceeds from the investment are optimally utilized for socio-economic projects. This study realizes as one of the pioneer endeavors to group Waqf fund via unit